Penerapan Game Based Learning berbantuan Wordwall pada Mata Pelajaran Informatika di SMAN 4 Padang - Ramadhani, Wahyuni; Marta, Rizkayeni; Asmara, Delvi; Zaus, Mahesi Agni (TSAQOFAH, 2025)
This study is motivated by the need for innovative learning strategies that can enhance student engagement and learning outcomes, particularly in Informatics subjects. The objective of this research is to analyze the effect of the Game Based Learning (GBL) model assisted by the interactive media Wordwall on the learning outcomes of Grade X students at SMA Negeri 4 Padang. A quantitative approach was employed using a quasi-experimental design with a nonequivalent control group design. The sample consisted of two classes selected through purposive sampling: the experimental class (X E 2), which implemented the GBL model with Wordwall, and the control class (X E 6), which used the Project Based Learning model. The research instruments included multiple-choice tests for both pre-test and post-test, which were tested for validity, reliability, item difficulty, and discrimination index. Data collection techniques included learning outcome tests and documentation, while data analysis involved normality tests, homogeneity tests, and independent sample t-tests using SPSS 27. The results revealed a significant difference between the learning outcomes of students in the experimental and control classes, with post-test average scores of 83.61 and 72.78, respectively. The study concludes that the GBL model assisted by Wordwall is effective in improving student learning outcomes and fostering an interactive and enjoyable learning environment. Therefore, this model is recommended as an alternative instructional strategy to enhance the quality of Informatics education at the secondary school level.